FRONT AND BACK MATTER VOL. 4 NO. 2 - Muizzu Nurhadi (Universitas 17 Agustus 1945 Surabaya, Prodi sastra Inggris, Fakultas Ilmu Budaya, 2021)
Front Matter Anaphora: Journal of Language. Literary, and Cultural Studies Volume 4 Number 2, December 2021